The t-Test and High-Order Serial Correlation: A Reply - Belsley, David A. (The Review of Economics and Statistics, 1974)
Belsley, D. A., The Power of the r-Test: Furthering Comment, this REvIEw, LV (Feb. 1973), 132. Cramer, H., Mathematical Methods of Statistics (Princeton: Princeton University Press, 1946), 290. Geary, R. C., Relative Efficiency of Count of Sign Changes for Assessing Residual Autoregression in Least Squares Regression, Biometrika, 57 (1970), 123. Habibagahi, H., and J. L. Pratschke, A Comparison of the Power of the Von Neumann Ratio, DurbinWatson and Geary Tests, this REVIEW, LIV (May 1972), 179. White, J. S., and J. A. Tillman, A Zero Crossing Statistic for a Gaussian Markov Process (mimeograph).